Olhares, construções: imagens sobre crianças do Ipiranga 1980-2000 - Araújo, José Luciano de (2007)
The following dissertation is based mostly in pictures, it explores the spaces, important occasions for the inhabitants in Ipiranga's district, São Paulo, in the lasts decades of the XX century. There we find images with children that shows significant moments and inclusion in the photographic albums. This research provides visibility to the childhood when analyzes the picture taken by eventual and professional photographers in residences, institutions like churches, school, nurseries, dispersed, in different collections. These photographers document infantile experiences, conditions of their lives, the strategies for the fight to resolv their problems in Sacomã's neiborhood, particularly, in São João Clímaco. Pictures were turned public in local newspapers, restricted to the private people, understood as visible memories proving the achievements in children's benefit. Records that today reveal people´s interests in the construction and preservation of narrative about infancies. Photographic collections that, when together, allow to realize the privileged moments to represent children, the picture popularization revealed by the perople of this group, permanences and changes in the thematic choices, the technological transformations in the machines and photographic supplies, the relationship of people with pictures about childhood, the records of new persons in district area that, until then, there wasn't win visibility. In the first chapter I write about the district as a scenery for pictures with children. The second chapter is about the institutions that creates pictures with children that were under their care, in the last I show the privileged situations in the photographic records, permanences and changes observed when pictures were compared